Pendampingan BTQ Anak Menggunakan Metode Bernyanyi Berbasis Media Visualisasi Di Korong Simpang Tiga - Zilfadlia Nirmala; Martin Kustati; Rezki Amelia (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2023)
The purpose of this assistance is to introduce and provide basic knowledge about hijaiyah letters, both in the form of readings and the basic forms of these letters. This assistance was carried out due to the lack of interest in reading and writing the Qur'an in Korong Simpang Tiga due to the Covid-19 situation and conditions that hit at that time. This assistance is carried out using the Particitpatory Action Research (PAR) method with the initial stage, namely by providing a general description by writing the hijaiyah letter shape on the blackboard, then introducing the reading by singing the song "hijaiyah letters". The next stage is to sing together by pointing one by one to the hijaiyah letters sung. The results of assistance in the first stage were obtained by children who previously did not know the hijaiyah letters, becoming aware of the hijaiyah letter shape by visualizing the shape of the letter on the blackboard. Then it was obtained that children who previously had little interest in learning the Qur'an became eager to learn by using the method of singing with the song "hijaiyah letters" and giving an idea of the shape of the hijaiyah letters. Then with the method of singing as well as visualizing the shape of the letters, it makes children who do not understand the differences between hijaiyah letters understand the differences between letters with one another. In using this method, children are also obtained who memorize and can write back the hijaiyah letters requested by the author.